Network pharmacology-based strategy to investigate pharmacological mechanisms of Tinospora sinensis for treatment of Alzheimer's disease. (15th September 2020) - Zhou, Feng; He, Kun; Guan, Yang; Yang, Xiyang; Chen, Yaohui; Sun, Mengsheng; Qiu, Xiaopeng; Yan, Feixia; Huang, Huilian; Yao, Lihua; Liu, Bo; Huang, Liping
Abstract: Ethnopharmacological relevance: Tinospora sinensis (Lour.) Merr. belongs to the family Menispermaceae. It is called LeZhe and is widely used as a kind of folk medicine especially in the Tibetan Plateau of China. T. sinensis has the functions of clearing away heat and detoxification, dispelling wind and dredging collaterals, calming and soothing the nerves. T. sinensis is an effective medicine for the prevention and treatment of aging diseases such as Alzheimer's disease (AD) in the Tibetan Plateau of China, whereas its material basis and underlying mechanisms are not clear. The aim of this study was to investigate the material basis and potential mechanisms of T. sinensis in the treatment of AD by using network pharmacology and molecular docking. Materials and methods: In this study, targets were collected from DrugBank database, Therapeutic Target Database (TTD) and literatures reports for the treatment of AD. Compounds were searched by literatures and systematic separation from T. sinensis . The molecular docking experiment was carried out by using Autodock Vina software to screen the bioactive compounds in T. sinensis and target proteins for AD. Then, the "compound-target network" was constructed by Cytoscape software. The drug-like properties of the active compounds were analyzed by pKCSM performs, and the protein-protein interaction (PPI) network was constructed by Search Tool for the Retrieval of Interacting Genes/Proteins (STRING). The Kyoto Encyclopedia of Genes and Genomes (KEGG) target pathway enrichment analysis was carried out by Database for Annotation, Visualization and Integrated Discovery (DAVID). Furthermore, the protective effect of neurons of two active compounds were verified with the injury cell model of PC12 and primary hippocampus neurons induced by Aβ25-35 . Finally, the key proteins of related pathways were quantitatively analyzed with Western blot method. Results: In total, 1 05 compounds and 38 targets have been screened. The main active compounds contained berberine, which belongs to alkaloids, Aurantiamide acetate, N–P-coumaroyltyramine, which belongs to amides, Trans-syringin and 3-demethyl-phillyrin, which belongs to phenylpropanoids. The targets covered inflammation-related proteins, including Protein kinase B (AKT), Phosphoinositide 3-kinase (PI3K), Tyrosine-protein kinase JAK1 (JAK1), mammalian target of rapamycin (mTOR), tumor necrosis factor alpha (TNF-α), Neuronal NOS (NOS1), and cholinergic function-related proteins, including α4-Nicotinic acetylcholine receptor (α4 nAChR), Muscarinic acetylcholine receptor M1 (Muscarnic M1). Inflammation and cholinergic dysfunction were the center of the network and occupy a dominant position. And the results of enrichment analysis shown the pathways mainly contained phosphoinositide-3-kinase/Akt (PI3K/Akt) signal pathway, neurotrophic factors (NTFs) signal pathway, Hypoxia-inducible factor 1 (HIF-1) signal pathway, mechanistic Target of Rapamycin (mTOR) signal pathway, Tumor necrosis factor (TNF) signal pathway, insulin resistance (IR). The results of in vitro assays showed that the tested compounds could significantly improve the survival rate and inhibit the apoptosis of PC12 cells and primary hippocampal neurons injured by Aβ25-35 . Western blot results showed that T. sinensis had a significant effect on the expression of protein PI3K and Akt. Conclusion : Our results revealed that T. sinensis could prevent and treat AD through a multi-compound-multi-target-multi-pathway regulatory network. Our work also expected to provide new ideas and theoretical bases for searching for the active compounds in T. sinensis and potential mechanism in the prevention and treatment of AD by the network pharmacology and molecular docking. The results of in vitro assay and in vivo assay supported the results of molecular docking. Graphical abstract: Image 1